2017
DOI: 10.1016/j.eats.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of the Pullout Repair of a Medial Meniscus Posterior Root Tear by Arthroscopic Centralization

Abstract: The meniscus roots are critical for meniscus function in preserving correct knee kinematics and avoiding meniscus extrusion and, consequently, in the progression of osteoarthritis. Several techniques exist for medial meniscus posterior root tear repair; however, current surgical techniques have been proved to fail to reduce meniscus extrusion, which has been shown to be associated with development of osteoarthritis, although significant improvements in the postoperative clinical findings have been achieved. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 8 publications
2
59
0
Order By: Relevance
“…A centralization technique has been developed to reduce meniscal extrusion; the capsule attached to the meniscus is sutured to the edge of the tibial plateau using suture anchors [13]. Arthroscopic centralization of the extruded lateral meniscus (LM) improved clinical outcomes at twoyear follow-up [14]. It also increased the radiographic lateral joint space width on standing at the 45°flexion view at 3 months; this was maintained for 2 years [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A centralization technique has been developed to reduce meniscal extrusion; the capsule attached to the meniscus is sutured to the edge of the tibial plateau using suture anchors [13]. Arthroscopic centralization of the extruded lateral meniscus (LM) improved clinical outcomes at twoyear follow-up [14]. It also increased the radiographic lateral joint space width on standing at the 45°flexion view at 3 months; this was maintained for 2 years [14].…”
Section: Introductionmentioning
confidence: 99%
“…Arthroscopic centralization of the extruded lateral meniscus (LM) improved clinical outcomes at twoyear follow-up [14]. It also increased the radiographic lateral joint space width on standing at the 45°flexion view at 3 months; this was maintained for 2 years [14].…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 , 5 , 6 , 7 , 8 , 9 Techniques have been described for centralization of the medial meniscus following root or radial tearing to address this issue. 13 The central tenet of these techniques is to restore the normal contact pressures and contact area to the compartment.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Meniscal extrusion decreased the tibiofemoral contact area and increased tibiofemoral contact pressure, leading to the worsening of knee osteoarthritis. 6 Koga et al 7,8 reported that arthroscopic centralization of the extruded meniscus, where the capsule adjacent to the meniscus was sutured to the edge of the tibial plateau, decreased meniscal extrusion. Arthroscopic centralization for an extruded lateral meniscus results in good clinical outcomes of the Lysholm knee scale and the Knee Osteoarthritis Outcome Score (KOOS) and radiographic outcomes with the lateral joint space widening at 2-years follow-up.…”
Section: Introductionmentioning
confidence: 99%